2020
DOI: 10.5650/jos.ess20083
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hexagonal Plate-like ZnO Single-crystal Particles in the Presence of Anionic Amphiphiles

Abstract: Inc. was used for pH adjustment. 6.20 g of SHS was added to 45 ml of ion-exchanged water and stirred at 343 K for 2 h. The resulting SHS solution, which was adjusted to pH 12 using the ammonia solution, was mixed with 10 ml of 2 M aqueous ZnSO 4 solution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The diffraction peaks of ZnO were observed in the XRD spectra of all samples 22,23) . The diffraction peak intensity of the (0 0 2) plane was remarkably higher than that of the other crystal planes because the addition of SHS suppressed crystal growth in the c-axis direction and facilitated crystal growth in the a-b-axis direction 16) . This indicated that the obtained samples had a high c plane orientation.…”
Section: Preparation Of Aunp/zno Composite Particlesmentioning
confidence: 96%
See 2 more Smart Citations
“…The diffraction peaks of ZnO were observed in the XRD spectra of all samples 22,23) . The diffraction peak intensity of the (0 0 2) plane was remarkably higher than that of the other crystal planes because the addition of SHS suppressed crystal growth in the c-axis direction and facilitated crystal growth in the a-b-axis direction 16) . This indicated that the obtained samples had a high c plane orientation.…”
Section: Preparation Of Aunp/zno Composite Particlesmentioning
confidence: 96%
“…[Zn (OH) 4 ] 2− was formed as an intermediate compound that decomposed as the reaction temperature increased and became a crystal growth unit for the ZnO particles (reaction 3) . The plate-like shape of the ZnO particles was the result of a change in the crystal growth rate owing to the adsorption of anionic surfactants on the c plane via electrostatic interactions 16) .…”
Section: Preparation Of Aunp/zno Composite Particlesmentioning
confidence: 99%
See 1 more Smart Citation